Administrative rights and obligations of the patient - Yosifova, Yoana (Law Journal of New Bulgarian University, 2022)
The medical administrative law is a field in the administrative property law – a special field, and regulates the public relations in the healthcare system in relation to: the activity of hospitals and similar medical bodies for hospitalization, diagnosis practices and treatment of patients with different conditions, the medical activities regarding the out-of-hospital emergency cases - consultation and treatment by practitioners competent in all fields of medicine, specialized doctors and surgeons as well as the dentists’ general and specialized practice, the relations between medical professionals and patients. The article displays the rights and duties of the patients. The analysis also considers the violation of improper exercise and implementation of various health rights and obligations that are related to administrative liability.